2020
DOI: 10.1093/cvr/cvaa307
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome and proteome mapping in the sheep atria reveal molecular featurets of atrial fibrillation progression

Abstract: Aims Atrial fibrillation (AF) is a progressive cardiac arrhythmia that increases the risk of hospitalization and adverse cardiovascular events. There is a clear demand for more inclusive and large-scale approaches to understand the molecular drivers responsible for AF, as well as the fundamental mechanisms governing the transition from paroxysmal to persistent and permanent forms. In this study, we aimed to create a molecular map of AF and find the distinct molecular programs underlying cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 64 publications
4
19
0
Order By: Relevance
“…We confirmed the occurrence of known AF factors like the reactivation of developmental pathways, but also found a strong and novel association with microRNAs and lncRNA from the DLK1-DIO3 locus, including the MEG3 canine orthologue. This finding is concordant with the many chromatin remodeling genes dysregulated in our models, which is an emerging phenotype of AF both in human and sheep models 35 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We confirmed the occurrence of known AF factors like the reactivation of developmental pathways, but also found a strong and novel association with microRNAs and lncRNA from the DLK1-DIO3 locus, including the MEG3 canine orthologue. This finding is concordant with the many chromatin remodeling genes dysregulated in our models, which is an emerging phenotype of AF both in human and sheep models 35 .…”
Section: Discussionsupporting
confidence: 89%
“…This is not observed in the AF group (lacking AVB), which may indicate that this adaptation has already occurred. This idea would be consistent with the down-regulation of chromatin-related genes recently noted in the atria of sheep AF models 35 , and may be a result of earlier establishment of profibrotic transdifferentiation in AF compared to AF+AVB canine models.…”
Section: Discussionsupporting
confidence: 85%
“…AF-SNPs in this locus lie within a gene desert where we and others found distal enhancer elements that interact with the promoters of PITX2 and ENPEP (34, 95, 96). On the one hand, PITX2 encodes a developmental TF expressed in the atria (97) found to be decreased in AF patients (98, 99) and in a sheep model of induced AF (100). On the other hand, ENPEP encodes aminopeptidase A, a member of the reninangiotensin system that cleaves angiotensin II to produce angiotensin III and is involved in hypertension (101).…”
Section: Discussionmentioning
confidence: 99%
“…Of those patients, most suffered from cardiovascular artery disease, valvular disease or heart failure, and in some cases, were under treatment for the previously mentioned or related comorbidities. In addition, although left atrial tissue has been demonstrated to undergo more profound remodeling [12] , the difficulty in J o u r n a l P r e -p r o o f obtaining left atria samples has led to an overrepresentation of right atrial tissue in published transcriptomic studies. Moreover, the collection of samples at different time points of disease progression is impossible for obvious reasons.…”
Section: Transcriptomics In Afmentioning
confidence: 99%
“…Several studies in goats, sheep and pigs show that artificially maintained AF leads to increasingly longer episodes of sustained arrhythmia [9,[179][180][181]. As an example of the potential of these induced AF animal models, we have recently described transcriptomic and proteomic changes during different stages of the disease in sheep and shown that most significant changes occurred at early stages of disease progression [12]. Moreover, goats are a well-established model of AF that has been used to test major pathophysiological signatures of the disease and the efficacy of antiarrhythmic drugs [182,183].…”
Section: Animal Models Of Afmentioning
confidence: 99%